Kajian Penerapan Konsep Arsitektur Modern Pada Gedung BPJS Kesehatan Cabang Lhokseumawe - I Taftazzani; A Dafrina; S Olivia (Jurnal MESIL (Mesin Elektro Sipil), 2024)
Lhokseumawe City is a stopover city for people from various regions. As a stopover city, Lhokseumawe has many buildings, including government buildings, educational buildings and also entertainment/shopping buildings or centers. Community activities in Lhokseumawe City are relatively dense, namely at the city government center. In this research the author used a descriptive qualitative method. This method focuses on the theoretical basis in order to avoid deviation from the discussion of this research. The author will observe directly or survey, then the survey results will be analyzed using a descriptive qualitative method that focuses on several points from the implementation of modern architecture. The BPJS Health Lhokseumawe Branch building uses modern material elements such as glass, iron and concrete layers. In terms of appearance, the BPJS building in Lhokseumawe City has a modern and functional appearance, with glass facade material maximizing natural lighting. The use of the facade on the BPJS Health Lhokseumawe Branch building is to give the impression of a modern building and provide natural lighting for the building to save energy. Planning for the BPJS Health building The Lhokseumawe branch is quite good at implementing modern architectural characteristics which reflect simple shapes, open facades, maximum natural lighting, use of modern materials such as concrete or glass, and the choice of neutral colors.